2003
DOI: 10.3136/fstr.9.364
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intestinal Dioxin Permeability Using Human Caco-2 Cell Monolayers

Abstract: A system to evaluate the intestinal permeability for 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) was constructed with human intestinal Caco-2 cell monolayers. TCDD was added to the apical side of the cell monolayers and the basal TCDD concentration was estimated by using a HepG2 cell having a luciferase vector with a xenobiotic-responsive element in the promoter region. Addition of such food substances as chlorophyll to the apical side of the Caco-2 cell monolayers markedly decreased the apical-to-basal transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In an earlier study the transport across a monolayer of Caco-2 cells of only 2,3,7,8-TCDD has been studied. 56 The authors quantified the TCDD concentration using a luciferase HepG2 cell assay. They found that 15% of TCDD was transported across the Caco-2 cell monolayer in 24 h. 56 This is higher than the 3% transported 2,3,7,8-TCDD observed by us for both models, which might be explained by differences in exposure concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study the transport across a monolayer of Caco-2 cells of only 2,3,7,8-TCDD has been studied. 56 The authors quantified the TCDD concentration using a luciferase HepG2 cell assay. They found that 15% of TCDD was transported across the Caco-2 cell monolayer in 24 h. 56 This is higher than the 3% transported 2,3,7,8-TCDD observed by us for both models, which might be explained by differences in exposure concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, despite the increased CFUs in BHI and Mac plates, the intestinal permeability as measured by FITC-Dextran was not increased (data not shown). In fact, TCDD could decrease the permeability to the Caco-2 cell monolayer in vitro (Natsume et al, 2003). Thus, TCDD could potentially have a beneficial effect on permeability because other AhR ligands increase mucus and anti-microbial peptide production by the host (Thorburn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain an experimental system with higher sensitivity and reproducibility, we constructed in the present study a stable dioxinresponsive cell line for a quantitative analysis. Good linearity of the dose-dependent increase in TCDD concentration of the basal solution was obtained in this work (Figure 3), whereas the basal TCDD concentration did not linearly increase when increasing the apical TCDD concentration from zero to 5 nM in the previous study (Natsume et al 2003). The better reproducibility and sensitivity of the present assay system by using stable transfected HepG2 cells enabled us to more accurately evaluate food substances for their TCDDabsorption inhibitory activity.…”
Section: Discussionmentioning
confidence: 58%
“…A differentiated Caco-2 cell monolayer expresses several features of intestinal epithelial cells (Hidalgo et al 1989) and it is widely used as an intestinal epithelial cell model. We have previously attempted to evaluate the amount of TCDD on the basal side of Caco-2 cell monolayers by using HepG2 cells transiently transfected by a plasmid with XRE sequences (Natsume et al 2003). However, this method was not suitable for quantitatively determining the intestinal permeability for TCDD, because the transfection efficiency varied each time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation